Perception of Auditors and Auditee on Public Sector Performance Audits - Widhi Setyo Pratama (Policy & Governance Review, 2019)
This study aims to discuss the perceptions of auditors and auditees on public sector performance audits. This study analyzes how social processes and interactions are both in the performance audit process. They are in case of changes in the auditor's role in the future, which have the potential to cause problems of independence. The other is that the benefits and impacts of performance audit results have not been felt significantly. By using a qualitative approach, this study analyzes how the perceptions and relations of the two actors in the performance audit. In-depth and structured interview techniques are used as data collection methods from participants from auditors and auditees. Auditee's response was also analyzed to determine the extent of their resistance to the actions of auditors and their perception of the benefits of performance audits. The results of the study show that performance audits have not given a significant impact on policy performance improvements. There are differences in perceptions about expectations for the role of the auditor and the provision of recommendations that are more solutive. A significant difference in perception is also shown in the auditor's understanding of the auditee's business processes. It is due to the issues in the auditor's qualifications and experience that are influenced by their educational background. Other findings are the potential disruption of auditor independence due to lack of operationalization of the concept of independence and the amount of pressure from the auditee.